Amyloid Pathology and Protein Kinase C (PKC): Possible Therapeutics Effects of PKC Activators - Ana Olariu; Kiyofumi Yamada; Toshitaka Nabeshima (Elsevier, 2005)
Amyloid β-protein (Aβ) is one of the most studied peptides in human neurodegenerative disorders. Although much has been learned about the biochemistry of this peptide, fundamental questions such as when and how the Aβ becomes pathologic remain unanswered. In this article we review the recent findings on the biology and pathology of Aβ and the role protein kinase C (PKC) plays in these processes. The potential neuroprotective role of PKC and the possible therapeutic effects of PKC activators in Alzheimer's disease (AD) will be discussed. Briefly, comments will be also addressed on the role of PKC in cell death and neurogenesis in AD. Keywords:: amyloid protein, Alzheimer's disease, signal transduction, protein kinase C, cell death